Analisis Bangkitan Perjalanan Mahasiswa Menuju Kampus Universitas Katolik Indonesia Santu Paulus Ruteng - Caling, Claudius Lippershey Bright; Cangkung, Arnoldus Otto F.; Gon, Kasmir; Sabu, Maria Kalista H.; Beyan, Eleonora Vilgia P.; Ihut, Karolina V. D.; Yudarsi, Pankrasio M.; Jo, Antonius A. (Portal: Jurnal Teknik Sipil, 2025)
This study aims to analyze the trip generation of students traveling to the campus of the Catholic University of Indonesia Santu Paulus Ruteng using a multiple linear regression statistical approach. Trip generation is a crucial aspect of transportation planning, especially in higher education areas with high mobility intensity. Data were collected through questionnaires distributed to 1,035 students from various study programs, determined using the Slovin formula with a 10% margin of error. This research examines respondent characteristics based on gender, mode of transportation, travel time, and the number of trips to campus per day. The results show that the most commonly used mode of transportation is motorcycles (42%), with the majority of students (63%) taking less than 15 minutes to reach campus, and 64% making only one trip per day. Regression analysis reveals that the number of classrooms and the campus land area simultaneously have a significant effect on the number of daily student trips, with an R Square value of 0.820. The t-test indicates that the number of classrooms has a significant positive effect, while the land area has a significant negative effect on trip frequency. These findings suggest that high academic activity, reflected in the number of classrooms, is the primary driver of student mobility. This study provides valuable input for data-driven campus transportation policy, which can be used to design an efficient, safe, and sustainable transportation system for the academic community.